REFLEKSI TERHADAP HUBUNGAN LEGISLASI: DEWAN PERWAKILAN RAKYAT DAN DEWAN PERWAKILAN DAERAH - toro, Iswan (Wacana Hukum, 2018)
AbstractThe journey of the Regional Representative Council (DPD) in the constitution is considered to still not compensate for the dynamics of proliferation of legislation. The reason is that the function of the DPD with the DPR in the field of legislation has been tugging and there has been intense competition in the formation of legislation, on the one hand the existence of the DPR as an institution holding a legislative function born earlier is considered to dominate the formation of legislation. On the other hand, the existence of the DPD as a new institution that is also given a legislative function, its authority is considered to be too small when compared to the authority of the DPR in the process of establishing legislation. Even the DPD is considered to add to the problem of over regulation in Indonesian legislation. Borrowing the term Richard Susskind mentions that hyper regulations or obesity are legal and over regulation. This situation led to the implementation of the DPD's legislative function not being optimal because it tends to be half-hearted. In other words, the existence of the DPD as the holder of legislative power is still under the shadow of the DPR, so it has not been taken into account in the process of establishing legislation in Indonesia, even though it has been corrected by the Constitutional Court through Decision of the Constitutional Court Number 92/PUU-X/2012 and Decision Constitutional Court Number 15/ PUU-XIII/2015, but the decision was ignored.AbstrakPerjalanan Dewan Perwakilan Daerah (DPD) dalam ketatanegaraan dianggap masih belum mengimbangi dinamika proliferasi legislasi. Penyebabnya adalah fungsi DPD dengan DPR di bidang legislasi mengalami tarik ulur dan terjadi persaingan ketat dalam pembentukan peraturan perundang-undangan, di satu sisi keberadaan DPR sebagai lembaga pemegang fungsi legislasi yang lahir lebih dahulu dianggap mendominasi pembentukan peraturan perundang-undangan. Sisi lain, keberadaan DPD sebagai lembaga baru yang juga diberi fungsi legislasi, kewenangannya dianggap masih terlalu kecil jika dibandingkan dengan kewenangan DPR dalam proses pembentukan peraturan perundang-undangan. Bahkan DPD dianggap akan menambah permasalahan over regulasi dalam peraturan perundang-undangan Indonesia. Meminjam istilah Richard Susskind menyebutkan bahwa hyper regulations atau obesitas hukum dan over rugulation. Keadaan tersebut menyebabkan pelaksanaan fungsi legislasi DPD tidak optimal karena cendrung setengah hati. Dengan kata lain, keberadaan DPD sebagai pemegang kekuasaan legislasi masih di bawah bayang-bayang DPR, sehingga belum diperhitungkan dalam proses pembentukan perundang-undangan di Indonesia, walaupun sudah diluruskan oleh Mahkamah Konstitusi melalui Putusan Mahkamah Konstitusi Nomor 92/PUU-X/2012 dan Putusan Mahkamah Konstitusi Nomor 15/PUUXIII/2015, namun putusan tersebut tidak dihiraukan.